Pengaruh Commitment Normatif, Keteguhan Kontinuan, Dan Perkembangan Jabatan Karir Kepada Hasil Kerja Karyawan (Studi pada PT Bankir Republik Indonesia (Perusahaan) Cab. Kota Malang Martadinata) - Zulfan Zulkarnaen Z; Budi Wahono; Muhammad Tody Arsyianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Those research aimed for determining the influence to normative commitment, continuity commitment and career development simultaneously Referring to the need for success in this research, this statistical analysis was carried out with a regression assessment (b1) = 0.716554 then accompanied by a tolerance assessment of 0.543, factors (career position development), and other factors that form freedom in the classical heteros test. has a detrimental value for the inter-factors in the independent variables in this experiment decreases. Furthermore, the regression assessment (b2) = 0.167, has the meaning of telling how a statement is considered capable of being used as an instrument. By having a valid conversation, it will form research that is useful for further research. Regression assessment (b3) = 0.118, explaining the meaning of the method of analyzing stacked data used for statistical production, explaining that with this explanation it can be explained carefully in terms of the factors that will be studied in the actual experiment. Furthermore, Based on the results of observations, where the development of career positions, they stated that focus and precision are needed in every activity. They learned this from previous corporations, so they can implement it within the company. Organizational culture with good program orientation from leaders will provide a real level of correlation in increasing the performance of PT employees. BRI of 82%, which explains the independent variables, namely Normative Commitment (X1), Continuous Commitment (X2), and Career Development (X3) is able to predict the dependent variable Employee Performance (Y). Then, the company's commitment to problem orientation can be realized in order to achieve the agreed goals of success of the work program. By achieving all agreed work programs, one factor for organizational success has been achieved. Keywords: Employee Performance, Normative Commitment, Continuity Commitment, and Career Development.